2003
DOI: 10.1046/j.1432-1033.2003.03560.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of novel salivary thrombin inhibitors from the ixodidae tick, Haemaphysalis longicornis

Abstract: Novel antithrombin molecules were identified from the ixodidae tick, Haemaphysalis longicornis. These molecules, named madanin 1 and 2, are 7-kDa proteins and show no significant similarities to any previously identified proteins. Assays using human plasma showed that madanin 1 and 2 dose-dependently prolonged both activated partial thromboplastin time and prothrombin time, indicating that they inhibit both the intrinsic and extrinsic pathways. Direct binding assay by surface plasmon resonance measurement demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(73 citation statements)
references
References 38 publications
3
68
2
Order By: Relevance
“…Furthermore, the sequence contained no cysteine residues, indicating that the protein had no threedimensional structures stabilized by disulfide bonds. These characteristics were similar to the thrombin inhibitory proteins that have been previously isolated from blood feeding arthropods [4,11,21,27].…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Furthermore, the sequence contained no cysteine residues, indicating that the protein had no threedimensional structures stabilized by disulfide bonds. These characteristics were similar to the thrombin inhibitory proteins that have been previously isolated from blood feeding arthropods [4,11,21,27].…”
Section: Resultssupporting
confidence: 74%
“…APTT is a screening assay for deficiency of coagulation factors associated with the intrinsic pathway of coagulation; on the other hand, PT is an assay for the extrinsic pathway. The above results indicated that chimadanin inhibited the blood coagulation factor that contributed to the common pathway of intrinsic and extrinsic coagulation pathways [11].…”
Section: Recombinant Protein Expressionmentioning
confidence: 76%
See 3 more Smart Citations